PENGEMBANGAN LKS BERBASIS KEUNGGULAN LOKAL PADA MATERI EKOSISTEM MATA PELAJARAN BIOLOGI KELAS X SMA/MA - Diana Novita Sari; Marhamah; Indra Himayatul Asri (Cocos Bio, 2022)
Abstract: This study aims to develop student worksheets based on excellence local in biology subject in ecosystem material in the tenth grade of senior high school. This type of Research is developmental research. The model used in this research and developmental is the Bord and Gall, it uses only five stages, namely: Research and information collecting, Planning, Develop preliminary form of product, Preliminary field testing, Main product revision. The validator consists of 1 material expert, 1 instructional material expert, and 2 biology teachers. The response consisted of 6 students of the eleventh grade of MA. Mu’allimin NW Pancor in the school year 2019/2020. The data collection technique use a questionnaire with a likert scale of 5 to 4, according to the researcher’s modifications. Data were analyzed using quantitative descriptive analysis techniques. Based on the results of data analysis and discussion, it can be concluded that the product of teaching materials in the form of developed worksheets has excellent criteria. Both in terms of material (94%), design aspect (95%), biology teachers (86,25%), and student responses (91,45%). Thus, those worksheets are approprivat for use in the learning process. Kata Kunci: Student’s Worksheets, Local Excellence. Ecosystem Abstrak: Penelitian ini bertujuan untuk mengembangkan Lembar Kerja Siswa (LKS) berbasis keunggulan lokal pada materi Ekosistem mata pelajaran biologi kelas X SMA/MA. Jenis penelitian ini adalah penelitian pengembangan. Model yang digunakan dalam penelitian dan pengembangan ini adalah model Bord and Gall dengan menggunakan 5 tahapan saja yaitu (Research and information collecting, Planning, Develop preliminary form of product, Preliminary field testing, Main product revision). Validator terdiri dari 1 ahli materi, 1 ahli bahan ajar, dan 2 guru biologi. Responden terdiri dari 6 orang siswa kelas XI IPA MA Mu’allimin NW Pancor tahun ajaran 2019/2020. Teknik pengambilan data menggunakan angket dengan skala likert 5 menjadi skala 4 sesuai modifikasi peneliti. Data dianalisis menggunakan teknik analisis deskriptif kuantitatif. Berdasarkan hasil analisis data dan pembahasan, dapat disimpulkan bahwa produk bahan ajar berupa LKS yang dikembangkan memiliki criteria sangat baik, baik dari segi materi (94%), segi desain bahan ajar (95%), guru Biologi (86,25%) dan respon siswa (91,45%). Dengan demikian, LKS ini layak digunakan dalam proses pembelajaran. Kata Kunci: Bahan Ajar LKS, Keunggulan Lokal, Ekosistem